Reporting of Bibliometric Reviews: Turkish Adaptation of the BIBLIO checklist - Özkan, Esra; Özsoy, Hatice; Çankaya, Askeri (Burdur Mehmet Akif Ersoy Üniversitesi, 2025)
Bibliometric analysis and bibliometric mapping use statistical tools and mathematical methods to provide quantitative and qualitative data to examine and evaluate studies around specific variables such as year of study, keywords used, number of citations, topics, authors, countries, and outcomes for organizations. Existing guidelines guide researchers to present findings from different study designs. To enhance the quality and transparency of health research, the EQUATOR guideline list includes checklists (Enhancing the Quality and Transparency of Health Research). Recently, it is observed that bibliometric analyses are rapidly increasing in the field of health. This study was conducted to translate the BIBLIO checklist added to EQUATOR into the Turkish language, to make it more understandable for researchers in bibliometric studies and to strengthen the reporting of bibliometric studies.

Bibliyometrik analiz ve bibliyometrik haritalama, nicel ve nitel verileri ortaya koymak adına istatistiksel araçlar ve matematiksel yöntemler kullanarak araştırmaların çalışma yılı, kullanılan anahtar sözcükler, atıf sayısı, konular, yazarlar, ülkeler ve kuruluşlara yönelik verilerin belirli değişkenler etrafında incelenmesi ve değerlendirilmesini sağlamaktadır. Farklı çalışma tasarımlarının bulgularını sunmak adına mevcut kılavuzlar araştırmacılara rehberlik etmektedir. Sağlık araştırmalarının kalite ve şeffaflığını artırmak için EQUATOR kılavuz listesinde kontrol listeleri (Enhancing the Quality and Transparency of Health Research) yer almaktadır. Son zamanlarda sağlık alanında da hızla bibliyometrik analizlerin arttığı gözlemlenmektedir. Bu çalışma, EQUATOR’a eklenmiş BIBLIO kontrol listesinin Türk diline kazandırılması, bibliyometrik çalışmalarda araştırmacılar için daha anlaşılır bir hale getirilmesi ve yapılacak olan bibliyometrik çalışmaların raporlanmasının güçlendirilmesi amacıyla yapıldı.
Bibliyometrik İncelemelerin Raporlanması: BIBLIO kontrol listesinin Türkçeye Uyarlaması
Keywords: Nursing (Other); Hemşirelik (Diğer)